Violent peace : militarized interstate bargaining in Latin America - Mares, David R. (New York : Columbia University Press, 2001)
-- Gabriel Marcella, U.S. Army War College.
Preface Interstate Competition in a Heterogeneous World: The Importance of Understanding Violent Peace -- The Issue -- The Origins of Violent Peace: Explaining the Use of Force in Foreign Policy -- Latin America's Violent Peace -- Analyzing Latin America's Violent Peace -- The Myth of Hegemonic Management -- Democracy, Restrained Leadership and the Use of Military Force -- The Distribution of Power and Military Conflict -- Military Leadership and the Use of Force: Illustrations from the Beagle Channel Dispute -- Democracies and the Use of Force: Suggestions from the Ecuador-Peru Dispute -- Militarized Bargaining in Latin America: Prospects for Diminishing Its Use.
Includes bibliographical references (pages 263-285) and index.
Print version record.
In English.
JSTOR
Keywords: Latin America -- Foreign relations; Conflict management -- Latin America; Latin America -- Military policy; Pacific settlement of international disputes; Gestion des conflits -- Amérique latine; Règlement pacifique des conflits internationaux; Amérique latine -- Relations extérieures.; Amérique latine -- Politique militaire; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; POLITICAL SCIENCE -- International Relations -- Diplomacy; Conflict management; Diplomatic relations; Military policy; Pacific settlement of international disputes; Latin America; Außenpolitik; Konfliktregelung; Lateinamerika; Geschichte 1900-2000.